2020
DOI: 10.3389/fmicb.2020.00787
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of Flagellar Export Chaperone FliS in Complex With Flagellin and HP1076 of Helicobacter pylori

Abstract: Functional flagella formation is a widespread virulence factor that plays a critical role in survival and host colonization. Flagellar synthesis is a complex and highly coordinated process. The assembly of the axial structure beyond the cell membrane is mediated by export chaperone proteins that transport their cognate substrates to the export gate complex. The export chaperone FliS interacts with flagellin, the basic component used to construct the filament. Unlike enterobacteria, the gastric pathogen Helicob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 51 publications
1
5
0
Order By: Relevance
“…2A ). In line with previous phenotypic studies ( 7 , 30 ), the cryo-EM images of the Δ fliY and FliY N strains revealed that none of the cells has flagellar filament. In addition, deformation of the cell membranes was observed in the ΔfliY strain (∼82% images) and the FliY N strain (∼80% images), as shown in Fig.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…2A ). In line with previous phenotypic studies ( 7 , 30 ), the cryo-EM images of the Δ fliY and FliY N strains revealed that none of the cells has flagellar filament. In addition, deformation of the cell membranes was observed in the ΔfliY strain (∼82% images) and the FliY N strain (∼80% images), as shown in Fig.…”
Section: Resultssupporting
confidence: 90%
“…The H. pylori wild-type strain G27, the Δ fliY strain, and the FliY N and FliY C complementation strains expressed with the N- or C-terminal domain of FliY, respectively ( 7 , 30 ) were inoculated into 10 mL of brucella broth supplemented with 10% heat-inactivated fetal bovine serum. The bacterial culture was grown at 37°C under microaerophilic conditions for about 24 h until the optical density at 600 nm reached ∼2.…”
Section: Methodsmentioning
confidence: 99%
“…However, the export process of glycosylated and non‐glycosylated FlaA was not tightly coupled with FliS chaperone binding, which was reported in a recent study in H . pylori G27 strain 35 . Their observation on the formation of short flagellar filaments in the Δ fliS mutant suggested a less efficient secretion of FlaA and impaired flagellar assembly.…”
Section: Discussionmentioning
confidence: 99%
“…pylori and other pathogens, 16,17,32‐37 it is likely that in the wild‐type strain (Figure 6, the left panel), PseE would first bind to FlaA, followed by sugar transfer to glycosylate FlaA. The glycosylated FlaA within this FlaA‐PseE complex would possibly be recognized by a flagellin‐specific chaperone FliS 33‐35 . With the chaperone‐mediated protection, the unfolded glycosylated FlaA would be transported efficiently via a flagellar type three secretion system (fT3SS) to extracellular surface.…”
Section: Discussionmentioning
confidence: 99%
“…However, for many bacterial pathogens, binding to mucus is a crucial step in their colonization. Flagella, composed of flagellin arranged in helical chains, are an important evolved strategy for mucus adhesion during infection by some pathogens, and they play a critical role in biofilm formation 17 . Enterotoxigenic E. coli (ETEC) strains are major causes of morbidity and mortality due to diarrheal illness in developing countries.…”
Section: The Gut Microbiome: Orchestrator Of the Mucus Barriermentioning
confidence: 99%